Overview on Pakistan R&D sector in context adopting technological capabilities - Zeeshan, Asim; Sarwat, Surriyya; Sorooshian, Shahryar; Ahmad, Muhammad Shahid (International Information Institute Ltd., 2017)
R&D driven firms plays a crucial role to starch a rapid growth in most emerging and even in developing economies. Because of dynamic business environment it's difficult to aligned nature of business with respect to fluctuating technological trends. Pakistan is skuggling in a global business domain because of lack of understanding regarding sustaining the technological capabilities in order to boost domestic industries for economic stability. A number of studies predominantly explore the concept of technological capabilities in the context of technology creation to technology acquisition. However, the establishment of technological capabilities always long term commitment. Based on the resource based-view theory this research article map the current R&D status of Pakistan with respects some of the emerging economies in the context of sustaining the technological capabilities. Finally, this paper will explore the information of potential limitations face by R&D sector in case of Pakistan.